Ziemiaństwo polskie a modernizacja gospodarki rolnej do 1914 r. (zarys problematyki) - Kita, Jarosław (Zeszyty Wiejskie, 2016)
The repressions that affected the Polish landowners after the defeat of the January Uprising and enfranchisement of the peasants in the Polish Kingdom, were carried out by the tsarist authorities and contributed to the crisis of this class of society. However, the economic problems of the landowners, should be sought much earlier. They were mainly caused by the lack of modernization of the farm economy among insurrections. Journalists associated with a landowners in the second half of the 19th century, started to publish a series of press texts and separate brochures, in which they tried to point out the causes of economic difficulties of landowners and indicate solutions to the problem. This paper aims to outline these issues, mainly based on origin of landowners. The article consists of four parts, titled: the causes of disease, diagnosis, recommendations, treatment. The analysis refers mainly to the Polish Kingdom, but also to other Polish lands under occupation.